2013
DOI: 10.3892/mmr.2013.1652
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid induced apoptosis and inhibition of proliferation in human acute promyelocytic leukemia HL-60 cells

Abstract: Chlorogenic acid (CA), is found in high abundance in the leaves of a number of plants and has antibacterial, antiphlogistic, antimutagenic, antioxidant and other biological activities. It reportedly possesses antitumor activity via the induction of apoptosis in chronic myelogenous leukemia (CML) cell lines, including U937 and K562 cells. However, the effects of CA on human acute promyelocytic leukemia (APL) HL‑60 cells remains unknown. In the current study, the ability of CA to cause G0/G1 cycle arrest and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 16 publications
3
59
0
1
Order By: Relevance
“…CGA has been used as a chemoprotective agent for chemotherapy in cancer patients by reducing the cytotoxic effects of anticancer drugs through scavenging reactive oxygen species (ROS) [20]. Also, a direct anti-tumor effect of CGA has been noted in various human cancer cells such as prostate cancer cells [21], acute and chronic myeloid leukemia cells [22,23], lung cancer cells [24], colon cancer cells and liver cancer cells [25]. Furthermore, CGA has been found to decrease urethane-induced lung cancer [26], the growth and progression of prostate cancer xenografts [21] and 12-Otetradecanoylphorbol-13-acetate (TPA) induced epithelial cancer in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…CGA has been used as a chemoprotective agent for chemotherapy in cancer patients by reducing the cytotoxic effects of anticancer drugs through scavenging reactive oxygen species (ROS) [20]. Also, a direct anti-tumor effect of CGA has been noted in various human cancer cells such as prostate cancer cells [21], acute and chronic myeloid leukemia cells [22,23], lung cancer cells [24], colon cancer cells and liver cancer cells [25]. Furthermore, CGA has been found to decrease urethane-induced lung cancer [26], the growth and progression of prostate cancer xenografts [21] and 12-Otetradecanoylphorbol-13-acetate (TPA) induced epithelial cancer in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most of studies reported that the pathogenesis of osteoporosis is associated with oxidative stress in osteoblasts [2, 3]. Overproduction of ROS disrupts the balance between oxidation and antioxidant defense systems, leading to bone loss by promoting lipid peroxidation and lowering antioxidant enzymes, inducing apoptosis of osteoblasts and inhibiting bone formation [46].…”
Section: Introductionmentioning
confidence: 99%
“…CGA, a type of polyphenolic compound formed by esterification of caffeic and quinic acids, is the major active ingredient found in many traditional Chinese medicines such as Flos Lonicerae Japonicae and Eucommia Ulmoides , and it is also abundant in some fruits, dietary vegetables, and daily beverages like coffee, pineapple, beans, strawberries and apples [23]. Previous reports have demonstrated that CGA exhibits a wide range of diverse pharmacological effects, including anti-inflammatory, anti-oxidative, and anti-carcinogenic activities [3, 24, 25]. However, the antioxidant effects and molecular mechanisms of CGA in osteoblasts have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Like other dietary polyphenols, CGA has numerous nutritional and pharmacological activities such as antidiabetes [15], antihypertension [16] and antitumor [17]. Importantly, CGA has also been recognized to possess various antiatherosclerotic activities, including hypolipidemic [18], [19], antioxidative [20], [21] and anti-inflammatory [22], [23] properties.…”
Section: Introductionmentioning
confidence: 99%